HIV epidemiology in Nigeria - Awofala, Awoyemi Abayomi; Ogundele, Olusegun Emmanuel (My University, 2018)
Nigeria realizes the devastating effects of HIV/AIDS on its people, health, economic, and social progress fairly recently. This paper analyses descriptively the HIV epidemiology in Nigeria based on the sentinel surveillance system in place. Recently, it is estimated that about 3, 229, 757 people live with HIV in Nigeria and about 220, 393 new HIV infections occurred in 2013 and 210,031 died from AIDS related cases. People practicing low-risk sex are the driving force of HIV epidemic in Nigeria while the high risk groups involving female sex workers, men who have sex with men and injecting drug users contribute substantially to new infections. In conclusion, HIV prevalence among adults in Nigeria is relatively low (3.2%), yet Nigeria is an enormous country where HIV infection remains an issue that demands a systematic and highly tailored intervention.
Keywords: AIDS; Epidemiology; HIV; Nigeria